Percepções sobre competência e mediação da informação no âmbito do acervo de livros digitais: estudo realizado nas bibliotecas do Instituto Federal do Ceará - Abreu, Patrícia Maria Honório (2020)
This research aims to understand the skills and processes of mediation of information to promote the collection of digital books in IFCE libraries. As a research problem, he proposed to know how the libraries of the Federal Institute of Education, Science and Technology of Ceará (IFCE) are articulating the competences and mediation processes necessary to promote the collection of digital books. Thus, it unfolds in the following specific objectives: to verify the mediation practices carried out by IFCE librarians regarding the promotion of the digital book collection and to identify what information skills the SIBI / IFCE librarians have to mediate the digital collection. In the methodology, exploratory, descriptive and qualitative quantitative research was used. To obtain the data, we opted for the electronic questionnaire with the librarians, elaborated and applied through the Google Forms tool. The content analysis technique was designed for data analysis and interpretation. The results showed that pedagogical mediation stands out in the face of technical and institutional mediation, prevailing in the responses of the participants, with more than 50%, the perception of user education, reference service, selective dissemination of information, social networks, information service utilities, products / services, website, e-mail and cultural actions as possible actions for information mediation. However, when analyzing professional practice, only the practice of educating users, social networks, e-mail and reference service is seen with a higher percentage of responses; the other options had results below 50%. In relation to competences, it appears that most of the skills needed by the individual competent in information are applied by librarians in the context of digital books in an eventual way. Thus, the indicators reveal that the best results were the ability to identify and handle potential sources of information effectively and efficiently, the habit of being proactive and lifelong learning. It is concluded that the typologies of information mediation, in digital contexts, need stimuli to be fully applied, as well as training for librarians, aiming at improving informational skills. Thus, competence and mediation of information are two essential intrinsic variables to promote books on digital platforms.